Analysis of Students’ Mathematical Reasoning in Solving Pythagorean Theorem Problems - Suyanti, Dwi; Waluyo, Mohamad (Urogram Studi Pendidikan Matematika, Universitas Ivet, 2024)
The purpose of this research is to describe students' understanding of the concept of the Pythagorean theorem. This research was carried out at Muhammadiyah 7 Bayat Middle School. This research uses descriptive qualitative research methods. The data collection technique is written test questions. The subjects of this research consisted of 20 class VIII students. The data analysis techniques used are data reduction, data presentation and conclusions. The results of this research were that 45% of students were able to solve questions on applying questions (C3), in the good category 25%, and 30% in the fair category. In the analysis questions (C4), 50% were in the very good category, 30% in the good category, and 20% in the fair category. In the evaluation questions (C5), 25% were in the very good category, 45% in the good category, and 30% in the fair category.